Analyse numérique et équations différentielles - Demailly, Jean-Pierre (Collection Grenoble sciences., 2006)
This title is an introduction to the analysis of signals through the technique of wavelets, a method which often lets the characteristics of the signals become more apparent than using the traditional decomposition in Fourier series.